A new approach in maximizing and direct utilization of whole Jatropha curcas L. kernels in biodiesel production – Technological improvement. (January 2016) - Go, Alchris Woo; Sutanto, Sylviana; Zullaikah, Siti; Ismadji, Suryadi; Ju, Yi-Hsu
Abstract: The direct ( trans )esterification of whole Jatropha curcas L. (JCL) kernels in subcritical solvent mixture of water, methanol and acetic acid was explored. A high fatty acid methyl ester (FAME) yield of 96.56% could be achieved at a solvent (water: acetic acid: methanol = 1:5:15, v/v/v) to solid ratio of 7 cm 3  g −1 . The reaction mixture was pressurize with carbon dioxide and reacted for 1 h at 523 K and 12.5 MPa. Qualitative tests on the recovered polar fractions of the product were found to have radical scavenging activities. The characteristics of the spent kernel residues were also studied. The method employed in this study provides an alternative approach to better utilize JCL kernels and cut down the number of production steps. Highlights: Direct utilization of whole Jatrpha curcas L. kernels. New approach in maximizing the utilization of Jatrpha curcas L. kernels. Preliminary characterization of by-products from in-situ transesterification.